Deuterium retention in tin (Sn) and lithium–tin (Li–Sn) samples exposed to ISTTOK plasmas. (August 2017) - Loureiro, J.P.S.; Fernandes, H.; Tabarés, F.L.; Mazzitelli, G.; Silva, C.; Gomes, R.; Alves, E.; Mateus, R.; Pereira, T.; Figueiredo, H.; Alves, H.
Highlights: Lithium and tin are two candidates for liquid metal plasma facing components. Using these materials depends on their compatibility with hydrogen plasmas. Samples of Sn and Li–Sn alloy where exposed at ISTTOK to deuterium plasmas. Deuterium retention was observed and was below 0.1 at.% for all samples. This suggests that Sn and Li–Sn make good candidates for plasma facing material. Abstract: The use of lithium (Li) or tin (Sn) as a liquid metal plasma facing component is proposed as a solution to the high power load issue on the divertor region of nuclear fusion reactors. The possibility to use these materials depends on their compatibility with hydrogen plasmas. With the purpose of realizing deuterium retention studies, specimens of pure Sn (99.999% Sn) and Li–Sn alloy (30 at.% Li) were exposed in the ISTTOK edge plasma. Ex situ analysis of the samples was performed by means of ion beam diagnostics. Nuclear reaction analysis (NRA) technique was applied using the D( 3 He, p) 4 He reaction to quantify the fuel retention on the samples. In this work the deuterium retention is compared between pure Sn and Li–Sn alloy samples in both liquid and solid states. All the samples were found to have retention ratios smaller than 0.1 at.%. This low retention ratio is expected for pure tin given its high mass and the instability of tin hydrides. However the retention was unexpectedly low for the case of Li–Sn which was thought to be dominated by the lithium fraction in the alloy. These results suggest that tin has a role in the retention mechanism in this material.